(3EOGQI GdeYQaI aj GdeDSSI GdEbJUGOjI (B((3GdLRA GdChd(B)s - (3YRGdOjf(B, (3SejQs ((3GdLRGFQs (3CLjGd GdQbejs, 2024)
(3JfGhdfG aj gPG GdcJGH eGjdj GdJCUjd GdfXQj dEOGQI GdeYQaI GdCSS hGdeaGgje, EOGQI GdeYQaI eONd eaGgjej hefWdbGJ fXQjI, JMdjd GdHfjI GdeYQajI dEOGQI GdeYQaI, EOGQI GdeYQaI hJMbjb GdejRI GdJfGaSjI aj GdHfhc GdLRGFQjI OQGSI MGdI Hfc GdhWfj GdLRGFQj, EOGQI GdeYQaI ceONd dHfGA GdejRI GdJfGaSjI, OhQ GbJUGO GdeYQaI aj JMbjb GdbOQI GdJfGaSjI, GSJQGJjLjI JOQjH GdehQO GdHTQj aj Xd EOGQI GdeYQaI, EOGQI GdeYQaI echfG LhgQjG dGSJQGJjLjI GdLhOI GdTGedI aj GdefXeI, CSGSjGJ GOGQI GdeYQaI, eJWdHGJ JWHjb feGPL GdGOGQI GdeYQajI aj efXeGJ GdCYeGd, GOGQI GdeYQaI ceONd dHfGA GdejRI GdJfGaSjI, OhQ fXQjI Ndb GdeYQaI GdJfXjejI aj GdJQSjN GdeaGgjej dEOGQI GdeYQaI, JMhjd hfbd GdeYQaI ef NdGd GSJQGJjLjI GdJYgjO, CKQ GdGaUGM GdeMGSHj Yf GdGSJKeGQ aj QCS GdeGd GdHTQj Ydi COGI GdeDSSI, OhQ eeGQSGJ EOGQI GdehGQO GdHTQjI aj JHfj GOGQI GdeYQaI, GdebGQHGJ GdfXQjI hGdJaSjQjI dEOGQI GdeYQaI, GdGSJKeGQ aj GdJYdje hJMOjGJ HfGA GbJUGO GdeYQaI, GOGQI GdeYQaI aj GdhbJ GdefGSH dOYe GdGSJLGHI ddCReGJ, (Bagner la guerre des talents comment rendre l'entreprise attractive et distinctive, The role of knowledge management in the continuous development of the future work of organizations(how to reach the level of good performance through knowledge management).s
Keywords: (3GOGQI GdeYQaIs; (3GdEOGQIs; (3Gdbhi GdYGedIs; (3GdeYQaIs